Effect of Seagrass on Current Speed: Importance of Flexibility vs. Shoot Density - Fonseca, Mark S.; Fourqurean, James W.; Koehl, M. A. R. (Frontiers in Marine Science, 2019)
Water flow through seagrass beds transports nutrients, affects sediment stability and chemistry, and imposes hydrodynamic forces on shoots that alter canopy configuration. Past studies done under diverse conditions yielded conflicting results about the effects of shoot density on flow through seagrass bed canopies. We used eelgrass, Zostera marina, to study how the density of flexible shoots affect the hydrodynamics of seagrass beds (canopies) in unidirectional water flow. By exposing randomly-arranged shoots of uniform length to current velocities controlled in a flume, the effects of shoot density and downstream distance (position) could be determined without confounding factors. Comparison of velocity profiles within beds to those upstream of the beds showed that flow was slower in the beds. However, shoot density, position, and current velocity did not affect the percent reduction in flow velocity in a (sea)grass bed. Turbulence enhances mixing of substances carried in the water. Here, turbulence intensity (index of the importance of turbulent velocity fluctuations relative to average current velocity) was lower when ambient flow was faster, but was not affected by shoot density or position, Drag, the hydrodynamic force on a shoot that bends it over in the flow direction, provides another measure of how the canopy affects flow experienced by a shoot. Drag was not affected by current velocity, shoot density, or position in the bed. Gaps between shoots can enhance light and flow penetration into the canopy, but when shoots are bent over by flow, they can cover gaps. Faster ambient currents caused greater gap closure, which at each current speed was greater for high shoot densities. Thus, canopy gap closure did not correlate with percent flow reduction in grass beds or with drag on individual shoots, both of which were independent of shoot density and ambient current velocity. Since changing shoot density does not affect the flow in a grass bed exposed to a given ambient current, our results are inconsistent with the hypothesis that the high shoot densities observed in grass beds in habitats exposed to rapid flow are due to a direct, adaptive response of the grass to the flow environment.